A hybrid compression-assisted absorption thermal battery with high energy storage density/efficiency and low charging temperature. (15th January 2021) - Ding, Zhixiong; Wu, Wei
Graphical abstract: Highlights: A novel hybrid compression-assisted absorption thermal battery is proposed. Three types of hybrid cycles are investigated and compared with the basic cycle. Dynamic characteristics and storage performance are presented and compared. A maximum storage density of 282.8 kW/m 3 is achieved by auxiliary compression. Better efficiency (0.66–0.71) is obtained with discharging process compression. Abstract: With worsening of global warming, environmental pollution, and energy crisis, the effective storage of renewable/waste energy has become a widely focused research topic. As an emerging thermal battery technology, absorption thermal energy storage aims to utilize low-grade energy for flexible applications (e.g., cooling, heating, dehumidification), which facilitates the matching between the energy supply and the energy demand. However, the current absorption thermal battery cycle suffers from high charging temperature, slow charging/discharging rate, low energy storage efficiency, or low energy storage density. To further improve the storage performance, a hybrid compression-assisted absorption thermal energy storage cycle is proposed in this work. Four thermal battery cycles, with/without compression in the charging/discharging processes, have been designed for comparisons. Dynamic characteristics and storage performance have been comparatively investigated by simulation using an experimentally validated model. Results show that the cycles with auxiliary compression can achieve a higher energy storage efficiency and density with a faster charging/discharging rate under a lower charging temperature. With a charging temperature of 80 °C, the energy storage efficiency and density are as high as 0.67 and 282.8 kWh/m 3 for the proposed compression-assisted cycle, while they are only 0.58 and 104.8 kWh/m 3 for the basic cycle. Moreover, the average charging and discharging rates of the compression-assisted cycle are 6.78 kW and 4.88 kW, respectively, which are also enhanced significantly compared to 1.88 kW and 1.27 kW of the basic cycle. This study could facilitate the development of absorption thermal battery with lower charging temperatures.